Comparative Effectiveness of Different Frequencies of Spinal Cord Stimulation for the Treatment of Patients with Failed Back Surgery Syndrome: Systematic Review and Network Meta-Analysis - Qin YY; Zhang CP; Tang SS; Wu JP; Zhu LX; Li YH; Xu F (Journal of Pain Research)
Yuan Yuan Qin,1,2,* Chun Pan Zhang,1,2,* Shun Song Tang,1,2 Jiang Ping Wu,1,2 Li Xuan Zhu,1,2 Yan Hua Li,1,2 Fei Xu1,2 1Department of Pain Management, The First People’s Hospital of Yunnan Province, Kunming, Yunnan, People’s Republic of China; 2The Affiliated Hospital of Kunming University of Science and Technology, Kunming, Yunnan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fei Xu, Department of Pain Management, The First People’s Hospital of Yunnan Province, 157 Jinbi Road, Kunming, 650032, People’s Republic of China, Email 494428530@qq.comPurpose: Failed back surgery syndrome (FBSS) is a common and challenging complication after lumbar spine surgery, with around 30% of patients experiencing this condition post-surgery. Spinal cord stimulation (SCS) is a prevalent treatment for FBSS, yet there is a lack of systematic comparisons among different SCS frequencies. This first network meta-analysis (NMA) compared the effectiveness and superiority of different SCS frequencies for FBSS.Material and Methods: Adhering to PRISMA guidelines, we searched PubMed, Web of Science, Embase, and CENTRAL for RCTs. Bayesian random-effects network meta-analysis assessed outcomes including pain reduction, functional capacity, and health-related quality of life.Results: This NMA (11 RCTs; n=2275) revealed efficacy variations among SCS modalities. Based on surface under the cumulative ranking (SUCRA) rankings, subperception SCS (500– 1200 Hz) had the highest probability for global pain relief (SUCRA=64.0%) and ≥ 50% pain reduction (SUCRA=75.3%; P < 0.05 vs low-frequency SCS). High-frequency SCS (10 kHz) was associated with higher SUCRA values for back pain (99.7%; P < 0.05 vs comparators; consistency χ²=1.41, P = 0.703) and leg pain (93.2%; P < 0.05 vs low-frequency SCS), suggesting a potential advantage. For functional outcomes, high-frequency SCS correlated with better ODI scores (SUCRA=85.0%), while subperception SCS showed higher probability for improved EQ-5D metrics (SUCRA=80.3%). All networks satisfied transitivity assumptions without significant inconsistency (P > 0.05).Conclusion: This NMA suggests potential differential therapeutic profiles among SCS modalities for FBSS. HF-SCS (10 kHz) showed relatively higher SUCRA values for back pain (99.7%), leg pain (93.2%), and disability improvement (ODI 85.0%). Subperception SCS (500– 1200 Hz) was associated with better probability for global pain relief (64.0%), ≥ 50% pain reduction (75.3%), and HRQoL outcomes (EQ-5D 80.3%). These findings warrant validation in head-to-head RCTs.Keywords: failed back surgery syndrome (FBSS), spinal cord stimulation (SCS), frequency, back pain, leg pain